IAPs: from caspase inhibitors to modulators of NF-kappaB, inflammation and cancer. - Gyrd-Hansen, M; Meier, P (2010)
The realization that alterations in inhibitor of apoptosis (IAP) proteins are found in many types of human cancer and are associated with chemoresistance, disease progression and poor prognosis, has sparked a worldwide frenzy in the development of small pharmacological inhibitors of IAPs. The development of such inhibitors has radically changed our knowledge of the signalling processes that are regulated by IAPs. Recent studies indicate that IAPs not only regulate caspases and apoptosis, but also modulate inflammatory signalling and immunity, mitogenic kinase signalling, proliferation and mitosis, as well as cell invasion and metastasis.